"Whole" vs. "fragmented" approach to EAACI pollen season definitions: A multicenter study in six Southern European cities. Issue 7 (11th May 2020) - Hoffmann, Tara Maria; Acar Şahin, Aydan; Aggelidis, Xenophon; Arasi, Stefania; Barbalace, Andrea; Bourgoin, Anne; Bregu, Blerina; Brighetti, Maria Antonia; Caeiro, Elsa; Caglayan Sozmen, Sule; Caminiti, Lucia; Charpin, Denis; et al.
Abstract: Background: The adequate definition of pollen seasons is essential to facilitate a correct diagnosis, treatment choice, and outcome assessment in patients with seasonal allergic rhinitis. A position paper by the European Academy of Allergy and Clinical Immunology (EAACI) proposed season definitions for Northern and Middle Europe. Objective: To test the pollen season definitions proposed by EAACI in six Mediterranean cities for seven pollen taxa . Methods: As part of the @IT.2020 multi‐center study, pollen counts for Poaceae, Oleaceae, Fagales, Cupressaceae, Urticaceae ( Parietaria spp. ), and Compositae ( Ambrosia spp., Artemisia spp.) were collected from January 1 to December 31, 2018. Based on these data, pollen seasons were identified according to EAACI criteria. A unified monitoring period for patients in AIT trials was created and assessed for feasibility. Results: The analysis revealed a great heterogeneity between the different locations in terms of pattern and length of the examined pollen seasons. Further, we found a fragmentation of pollen seasons in several segments (max. 8) separated by periods of low pollen counts (intercurrent periods). Potential monitoring periods included often many recording days with low pollen exposure (max. 341 days). Conclusion: The Mediterranean climate leads to challenging pollen exposure times. Monitoring periods for AIT trials based on existing definitions may include many intermittent days with low pollen concentrations. Therefore, it is necessary to find an adapted pollen season definition as individual solution for each pollen and geographical area. Abstract : Depending on the criteria used, the length of a pollen season can vary dramatically. EAACI criteria generate very extended pollen seasons in Southern Europe, which also include many days/weeks with no/low pollen counts. The exclusion of "intercurrent periods" with no/low pollen counts ("fragmented pollen season" method) improves the accuracy of EAACI criteria.